ANALISIS SIFAT MEKANIK KEKUATAN BAJA TULANGAN POLOS HASIL PROSES PERLAKUAN PANAS FASA GANDA - Riyanto Hery Nugroho (Universitas Lambung Mangkurat, 2014)
The increasing demand of reinforcing steel plain in the field used for the construction of housing will require the development of the structure of new materials for lightweight material but has a high tensile strength that is expected to lower production costs.The purpose of the study is to obtain information about: changes in the mechanical properties, especially the strength of the reinforcing steel plain experiencing double-phase heat treatment process. The extent to which changes in elongation deformation plain rebars are experiencing double-phase heat treatment process.The highest tensile reached 855.093 MPa with an increase of 44.69% change, the increase in the highest yield reached 672.751 MPa with increase in change of 58.94%. The results show a change in tensile strength, yield strength of reinforcing steel plain after a heat treatment process of dual phase both in terms of the diameter plain reinforcing steel and dual-phase temperature. The increase in power of 67% compared to before being subjected to a double phase tensile strength (ultimate) amounted to 595.732 MPa and a yield strength of 415.615 MPa. Besides the change of tensile strength and elongation yield are also changing. Where elongation decreased ability their after undergoing a process of dual-phase heat treatment. The decrease in elongation before treatment process multiple phases of 42.664% on the diameter of 8 mm to 35.226% at a temperature of 770oC dual phase treatment. Keywords: deformation, dual phase, plain steel reinforcement